A new species of Opistheurista Carvalho, from Southern Brazil (Heteroptera: Miridae: Mirinae) - Ferreira, Paulo S.f.; Coelho, Lívia A. (Zootaxa, 2006)
The Resthenini genus Opistheurista has been known until now by the single species O. clandestina, which occurs in the Nearctic region. While studying mirids from Rio Grande do Sul, Brazil, we found a female exemplar as a new species. We provide descriptions, diagnoses, illustrations, and a key to distinguish the two species of genus Opistheurista.